Spatial transcriptomic differences in the breast muscle of grower broilers at 21 and 28 days of age - Janghan Choi; Jihwan Lee; Doyun Goo; Gippeum Han; Venkata Sesha Reddy Choppa; Seshidhar Reddy Gudidoddi; Majid Shakeri; Hong Zhuang; Brian Bowker; Woo Kyun Kim; Byungwhi Kong (Poultry Science)
This study investigated transcriptomic differences between the caudal and cranial areas in breast muscle in the grower phase of broiler chickens (D 21 and D 28). A total of 66 one-day-old broiler chickens were allotted to 6 cage pens of 11 birds per pen. On D 21 and D 28, one bird per pen was randomly selected, and breast muscle samples were collected in the caudal and cranial areas of the Pectoralis major. RNA sequencing was conducted, followed by screening for differentially expressed genes (DEGs; P < 0.05) and multivariate analyses. A total of 24,498 genes were identified, and 8,831 genes had greater than 100 mean read count. On D 21, there were 666 DEGs, among which 482 and 184 genes were down-regulated and up-regulated, respectively, in the caudal area compared with the cranial area. There were 2 down-regulated and 56 up-regulated genes with a greater than 1.5-fold change (FC). On D 28, there were 872 DEGs, among which 408 and 464 genes were down-regulated and up-regulated, respectively. There were 12 down-regulated and 23 up-regulated genes with a greater than 1.5-fold change. Principal component analysis (PCA) plots showed that gene profiles were not distinctly separated between the caudal area and the cranial area of breast muscle on D 21 and D 28. On D 21, collagen type XI alpha 1 chain (COL11A1), fibromodulin (FMOD), myosin heavy chain 7B (MYH7B), carbonic anhydrase 3A (CA3A), tenomodulin (TNMD), COL12A1, carboxypeptidase Z (CPZ), lysyl oxidase like 2 (LOXL2), COL1A1, and COL1A2 were significantly down-regulated in the caudal area compared to the cranial area with a greater than 2-FC (P < 0.05). KEGG pathway enrichment analysis indicated that various pathways including regulation of actin cytoskeleton, ribosome, and focal adhesion were significantly different in the caudal area compared with the cranial area. These findings suggest that spatial differences in gene expression within the breast muscle could be linked to functional or developmental variations between regions, potentially influencing muscle growth, meat quality, and breast myopathies. Understanding these spatial transcriptomic differences may provide insights into identifying etiologies and developing strategies for breast myopathies.